Apelin Levels and its Relationship with a Number of Electrolytes in Patients with Myocardial Infarction - Mousa J. Humesh; AbduL-Monaim H.M. AL-Samarraie; Zainab A.L. AL-Samarraie (Tikrit Journal of Pure Science)
The study aimed to determine the effect of the lack of Apelin peptide and its relation to the development and severity of coronary atherosclerosis and to prove its association with acute myocardial infarction and the positive effect when increasing its concentration in the body and protect it from various diseases. The study included 70 patients of different ages infected with myocardial infarction, both high blood pressure and diabetes, were significantly presented in the group of patients in this study and were compared with control group, which included 35 samples of healthy people. The study showed that there was a significant decrease (P≤0.05) in Apelin concentration in people who suffered from myocardial infarction compared with the control group, which was their Apelin concentrations within the normal rates, there was a significant decrease (P≤ 0.05) in the concentration of Apelin with males and females who suffered from myocardial infarction compared with males and females in control group, which was within normal concentrations that existed in the blood, parameters were measured the concentrations of Apelin and the results of study as follows: There was a significant decrease (P≤0.05) in the concentration of sodium, potassium, chloride and magnesium ions in patients with myocardial infarction compared with the control group. The concentrations of electrolytes in the sera of males and females were significantly decreases (P≤0.05) in regard to sodium, potassium and chloride ions in males and females patients compared to control group, while there were no significant differences (P≤0.05) in the concentration of magnesium between males and females of patients and control group. The correlation of sodium, potassium, magnesium and chloride ions with the concentration of the Apelin was positive. It rises continuously with elevation in the concentration of the Apelin and decrease in the concentration of Apelin. This has a positive effect on myocardial function and improve its function.